2002
DOI: 10.1034/j.1600-0447.2002.0_011.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of plasma atrial natriuretic peptide in protracted alcohol withdrawal

Abstract: We suggest that a dysregulation of ANP plasma levels during alcohol withdrawal may contribute to symptoms of protracted withdrawal such as craving and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
(39 reference statements)
0
27
0
2
Order By: Relevance
“…Concerning ANP, a peptide repeatedly shown to be involved in the pathophysiology of withdrawal [4,30], we detected a significant hypomethylation of the ANP gene promoter region on day 7 in alcohol-dependent patients compared to healthy controls. These results again are in line with the results of Hillemacher et al [3], who reported a decreased promoter-related DNA methylation of ANP combined with a significantly elevated ANP mRNA expression in alcohol-dependent patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Concerning ANP, a peptide repeatedly shown to be involved in the pathophysiology of withdrawal [4,30], we detected a significant hypomethylation of the ANP gene promoter region on day 7 in alcohol-dependent patients compared to healthy controls. These results again are in line with the results of Hillemacher et al [3], who reported a decreased promoter-related DNA methylation of ANP combined with a significantly elevated ANP mRNA expression in alcohol-dependent patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 58%
“…We expect this to be an immediate response to detoxification without prolonged effects on overall protein expression. As ANP is not directly involved in the metabolism of ethanol but postulated to have a role in the pathophysiology of alcohol withdrawal [4], finding serum levels of ANP unchanged is yet another indication of a more complex regulation than proposed. This perspective is also reflected in the literature; while Kiefer et al [4] reported reduced ANP levels in the patient group during acute alcohol withdrawal compared to healthy controls, Döring et al [5] observed a persistent ANP elevation in recently abstinent alcoholics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulation of ANP plasma levels have been implicated in the pathophysiology of depression and protracted alcohol withdrawal (Kiefer et al, 2002;Strohle and Holsboer, 2003). Elevated plasma levels of ANP have been reported in women suffering from AN (Ohashi et al, 1988) as well as an impaired response of ANP to an acute water load (Baranowska et al, 1995).…”
Section: Introductionmentioning
confidence: 99%